Response of transplanted fennel (Foeniculum vulgare Mill.) to potassium fertilization - Bhardwaj, R L (Journal of Spices and Aromatic Crops, 2016)
This study presents the results of farmer’s field experiment on the effects of potassium (K) fertilization on transplanted fennel (Foeniculum vulgareMill.) production. Four treatments (K1 = 20 kg K ha-1, K2 = 40 kg K ha-1, K3 = 60 kg K ha-1, K4 = 80 kg K ha-1) were compared using four replications under Completely Randomized Design. Application of potassium @ 60 kg ha-1 recorded highest value of plant height primary branches plant-1, secondary branches plant-1, number of leaves, number of roots plant-1, tap root length, fresh weight of shoot, fresh weight of root and minimum root: shoot ratio. The maximum value of number of umbels plant-1, umbellate umbel-1, number of seeds umbel-1, test weight, seed yield, straw yield and harvest index was also observed in same treatment. All the quality parameters like, volatile and total oil content, soluble sugar, total carbohydrate, crude protein, potash content of seed and soil and overall quality of seeds were higher with application of 80 kg K ha-1, whereas disease incidence was significantly reduced with application of higher dose of K. The maximum gross return, net return and highest benefit: cost ratio was also recorded with application of 60 kg K ha-1.